Factors affecting accounting students in choosing careers as public accountants - Selvi Aristantya (International Journal of Applied Finance and Business Studies, 2023)
This study aims to determine the influence of motivation, financial rewards, and professional recognition on the career selection of accounting students in accounting students of the Indonesian Institute of Business and Computer Affairs. This research uses quantitative data types and data sources which are primary data obtained from accounting students of the Indonesian Institute of Business and Computers. The sampling technique of this study is a census where the number of samples in this study is as many as 60 respondents. Data analysis used with the Partial Least Square (PLS) approach. Where PLS is a model of Structural Equation Modeling (SEM) equations based on variations or components. The results of this research are motivation and Financial rewards influence accounting students' career choices as public accountants. Professional recognition does not influence accounting students' career choices as public accountants.